Fazzan in Modern History - Ahmad Ahmad Sayyid Ahmad (Journal of Islamic Studies, 1981)
This study concerns the Libyan region of Fazzan in modem history, from 1550 to 1951. In the opening years of this period, Muhammad al-Fasi, of Moroccan origin, declared himself sultan in Fazzan, while in the second year mentioned, Libyan independence was announced. Between those two years, events of great importance occurred.